Experimental Estimation of the Heat Transfer Coefficient of an Unglazed Solar Plate for Unsteady Humid Outdoor Condition. (13th September 2021) - Uba, Felix; Essandoh, Eric Osei; Akolgo, Gilbert Ayine; Opoku, Richard; Oppong-Kyereh, Lawrence; Gyimah, Eric Anokye
Abstract : This research presents a study on the heat transfer coefficient for an unglazed solar plate collector in an unsteady humid outdoor environment. The purpose for undertaking this research is to investigate the correlation between the heat transfer coefficient and air speed and also verify whether heat transfer from unglazed solar thermal collectors under outdoor conditions can be experimentally determined using a particular mathematical relationship for different locations. In estimating the heat transfer coefficient for an unglazed solar plate in an unsteady humid outdoor condition, an experiment was held using an outdoor setup that measured temperatures, wind speeds, and solar radiations from 11:00 A.M. to 2:00 P.M. The solar plate collector was placed on a flat bed of height 2.2 m and a collection area of 0743 m 2 . An average temperature of 45°C was recorded for a mild steel plate collector which was initially exposed to an ambient temperature which ranges from 25°C to 32°C. The interfacial temperature between the plate and an asbestos board ranges from 42°C to 52°C, and that of the asbestos and a plywood is 40°C to 46°C. The specific heat capacity of the mild steel plate and the asbestos board used for the construction of the experimental setup are 25.00 kJ/kg and 950.00 kJ/kg, respectively, while the thermal conductivity of these materials is 0.46 W/m·K and 0.25 W/m·K, respectively. The novelty of this work is the use of such a study to generate empirical equations for Ghana and to produce representative equations for determining the heat transfer coefficient for solar plate collectors in unsteady humid outdoor conditions in West Africa. This work is expected to contribute data alongside similar works done for different areas to help propose empirical equations for estimating global and not site-specific heat transfer coefficients.